IMPACT OF AN ULTRA-MARATHON OF 330 KM ON PLASMA LEVELS OF CARDIAC BIOMARKERS. Issue 4 (1st February 2017) - Goff, Caroline Le; Kaux, Jean-François; Gergelé, Laurent; Millet, Grégoire P; Giardini, Guido; Viallon, Magalie; Croisille, Pierre; Cavalier, Etienne
Abstract : Background: While a moderate exercise benefits on the cardiovascular system, consequences of a supraphysiological effort are not yet clear. Objective: The aim of our study was to evaluate the consequences of an ultra-marathon on cardiac and muscles markers (CK, myoglobin, hsTnT, NT-proBNP, copeptin, H-FABP) but also markers of inflammation CRP DFO, GB) and of renal function (urinary NGAL and plasma and urinary creatinine). This project also studied the evolution of new cardiac fibrosis biomarkers: ST2 and Gal-3. Design: Longitudinal, cohort study. Setting: The Tor des Geants (TdG), a 330 km long ultra distance trail running, with +24, 000 m elevation changes in the Valley of Aosta (Italy), is considered as one of the most difficult mountain marathon race in the world. The maximum time allowed to complete the race is 150 h. Patients (or Participants): 51 participants attending the TdG have been followed and the study was conducted on 33 subjects having reached at least half of the race (148.7 km). Interventions (or Assessment of Risk Factors): Repeated blood and urine samples collection were carried out at four key time points: before, during (mid-point) and after the race (less than 1 h) and 3 days after the end of the race. Main Outcome Measurements: Biological samples were collected at these four different times. Several biomarkers were assayed on different analyzers such COBAS®, KRYPTOR®, VIDAS® and ETIMAX®, meanwhile, the ST2 and Gal-3 were measured manually. Results: During the TdG, the plasma levels of cardiac markers, muscle and inflammation have increased significantly to halfway. Meanwhile, the markers of renal function have only slightly varied, excepting plasma creatinine. Conclusions: The study suggests that there is no permanent structural damage at the myocardium level. However, the low pace adopted by the tired runners caused an inflammatory response as well as muscle damage less important than a shorter race.